2016
DOI: 10.1089/neu.2015.4229
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Polypeptide Ameliorates Mild Traumatic Brain Injury-Induced Cognitive and Sensorimotor Deficits and Neuroinflammation in Rats

Abstract: Mild traumatic brain injury (mTBI) is a major public health issue, representing 75–90% of all cases of TBI. In clinical settings, mTBI, which is defined as a Glascow Coma Scale (GCS) score of 13–15, can lead to various physical, cognitive, emotional, and psychological-related symptoms. To date, there are no pharmaceutical-based therapies to manage the development of the pathological deficits associated with mTBI. In this study, the neurotrophic and neuroprotective properties of glucose-dependent insulinotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 104 publications
(100 reference statements)
2
16
1
1
Order By: Relevance
“…To this end, incretins and incretin mimetics have been investigated in regard to their anti-apoptotic, neuroprotective and neurotrophic effects in neurons expressing incretin receptors: namely the glucagon-like peptide 1 (GLP-1) receptor (GLP-1R) and the glucose-dependent insulinotropic peptide (GIP) receptor (GIPR) (Rachmany et al, 2013b; Tweedie et al, 2013a; Li et al, 2015; Tweedie et al, 2016; Yu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…To this end, incretins and incretin mimetics have been investigated in regard to their anti-apoptotic, neuroprotective and neurotrophic effects in neurons expressing incretin receptors: namely the glucagon-like peptide 1 (GLP-1) receptor (GLP-1R) and the glucose-dependent insulinotropic peptide (GIP) receptor (GIPR) (Rachmany et al, 2013b; Tweedie et al, 2013a; Li et al, 2015; Tweedie et al, 2016; Yu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of mTBI is complex and characterized especially by neuronal cell death and axonal damage induced primarily by the direct physical impact itself and secondarily by oxidative stress, neuroinflammation, mitochondrial dysfunction, DNA damage, and other pathological processes (Maas et al, 2008;Choe, 2016;McInnes et al, 2017). Since incretins have the capability to intervene in more than one of these pathological events (Perry et al, 2002;Nyberg et al, 2005;Iwai et al, 2006;Li et al, 2010b;Paratore et al, 2011;Yu et al, 2016;Verma et al, 2017), incretin mimetics have the potential to serve as neuroprotective agents following mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, incretin analogs have been efficacious in preclinical models of: (i) Alzheimer's disease (Li et al, 2010a;McClean et al, 2011;Faivre and Holscher, 2013), (ii) Parkinson's disease (Bertilsson et al, 2008;Li et al, 2009Li et al, , 2016, (iii) stroke and ischemia (Li et al, 2009;Hyun Lee et al, 2011), (iv) peripheral neuropathy (Perry et al, 2007), (v) amyotrophic lateral sclerosis (Li et al, 2012), (vi) Huntington's disease (Martin et al, 2009), and (vii) TBI (Rachmany et al, 2013;Li et al, 2015;Yu et al, 2016;Tamargo et al, 2017;Bader et al, 2019). Moreover, as marketed GLP-1 analogs to treat T2DM are well-tolerated and rarely cause hypoglycemia, clinical trials have been undertaken to investigate the therapeutic effects of exendin-4 or liraglutide on Alzheimer's disease (Egefjord et al, 2012;Gejl et al, 2016), and Parkinson's disease patients (Aviles-Olmos et al, 2013;Athauda et al, 2017), and continue to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These group B receptors additionally include GPCRs that selectively bind glucose-dependent insulinotropic peptide (GIP), vasoactive intestinal peptide (VIP), pituitary adenylyl cyclase-activating peptide (PACAP) and other peptides (Harmar 2001; Nadkarni et al, 2014), several of which have demonstrated neuroprotective actions (Dejda et al, 2005; Brenneman 2007; Li et al, 2016; Yu et al, 2016). Heterotrimeric stimulatory (Gs) GTP-binding proteins are activated in response to GLP-1R and GCGR agonist binding, and they couple agonist occupancy to the stimulation of transmembrane adenylyl cyclases that in neurons, like pancreatic β-cells, catalyze conversion of ATP to cytosolic cAMP, a second messenger that then activates key downstream proteins (Campbell and Drucker, 2013; Nadkarni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%